Aktualisasi Budaya Organisasi Madrasah dalam Meningkatkan Kinerja Guru - Huda, Mualimul (Jurnal Penelitian, 2021)
Madrasah is part of educational organizations that provide Islamic education. Madrasah continues to innovate and reform in their implementation to become educational institutions that have advantages and can compete in the midst of globalization.. One form of effort to improve teacher performance is the actualization of madrasah organizational culture, which is reflected in aspects of values and norms that are believed to be true, attitudes and behavior of madrasah residents, and all habits traditions that are internalized with educational programs in Madrasah. This study aims to describe the organizational culture of madrasah by referring to the concept of theory, descriptive analysis to improve teacher performance. The method in this reseach used an approach mixed method. Data collection techniques through questionnaires, documentation, interviews, and observation instruments. The data are presented with quantitative descriptive analysis accompanied by qualitative descriptive analysis. Respondents and informants in this research were selected through cluster sampling, which consisted of madrasah principals, teachers, and private madrasah aliyah committees in Jepara. This study describes that the achievement of madrasah organizational culture in the dimensions of values, attitudes, and habits reaches an average value in the excellent category. It is necessary to increase the collaboration indicators between teachers and appreciate the performance. There are organizational cultural values that are believed to be a form of worship and a spirit of devotion (hidmah), and prioritize education based on exemplary, habituation of religious activities and the formation of ahlakul karimah.